2022
DOI: 10.1101/2022.10.07.511266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Talin and kindlin cooperate to control the density of integrin clusters

Abstract: Focal adhesions are important mechanosensitive structures, composed of transmembrane integrins, linking the extracellular matrix to the actomyosin cytoskeleton, via cytoplasmic proteins. Cellular adhesion to the extracellular matrix depends on the activation of integrins by intracellular mechanisms. Talin and kindlin are major activators of integrins that are recruited to the inner membrane and bind to Beta-integrin cytoplasmic tails. Many studies showed the importance of integrin activation and clustering and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Talin variants appended with a C-terminal hexahistidine (His 6 ) were purified as described elsewhere [6]. CdSe/CdS/CdZnS/ZnS core/multishell QDs were prepared and coated with CL4 capping ligands as described previously [45].…”
Section: Fret Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Talin variants appended with a C-terminal hexahistidine (His 6 ) were purified as described elsewhere [6]. CdSe/CdS/CdZnS/ZnS core/multishell QDs were prepared and coated with CL4 capping ligands as described previously [45].…”
Section: Fret Biosensorsmentioning
confidence: 99%
“…Talin is largely responsible for the mechanosensing of FA [4]. This protein directly binds FA receptors (integrins) and phosphatidylinositol 4,5-bisphosphate (PIP2) lipids on the membrane [5], [6]. Filamentous actin binds to the distal end of Talin and with myosin exerts a pulling force [7], triggering the maturation of focal adhesions [4].…”
Section: Introduc:onmentioning
confidence: 99%
“…Talin is largely responsible for the mechanosensing of FA [4]. This protein directly binds FA receptors (integrins) and phosphatidylinositol 4,5-bisphosphate (PIP2) lipids on the membrane [5], [6]. Filamentous Actin binds to the distal end of Talin and with Myosin exert a pulling force [7], triggering the maturation of focal adhesions [4].…”
Section: Introduc:onmentioning
confidence: 99%
“…Its head domain binds to the cell plasma membrane. On the one hand, it interacts with inositol phosphate groups [5], [6] of phosphatidylinositol 4,5-bisphosphate (PIP 2 ) lipids at the plasma membrane, releasing Talin autoinhibition [7], [8]. Interestingly, it was demonstrated that F 3 interacts with R 9 and F 2 with R 12 , resulting in an inactive snake like biting its own tail conformation [6], [9].…”
Section: Introductionmentioning
confidence: 99%